2020
DOI: 10.1111/eos.12732
|View full text |Cite
|
Sign up to set email alerts
|

Composition of hemidesmosomes in basal keratinocytes of normal buccal mucosa and oral lichen planus

Abstract: Oral lichen planus (OLP) is a chronic inflammatory disease displaying ultrastructural disturbances in epithelial hemidesmosomes. The expression of several key hemidesmosomal components in OLP as well as in normal buccal mucosa is, however, unknown. The aim of the study was therefore to examine intracellular and extracellular components involved in hemidesmosomal attachment, in OLP (n = 20) and in normal buccal mucosa (n = 10), by immunofluorescence. In normal buccal mucosa, laminin‐α3γ2, integrin‐α6β4, CD151, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Hemidesmosomes are anchoring structures at the basement membrane that link intermediate filaments with the extracellular matrix via integrin proteins [20]. These types of junctions have been found in most of our major organs, including the epithelium of the skin [21][22][23][24][25], the digestive system (oral cavity, esophagus, stomach, and intestine) [26][27][28][29][30][31][32][33][34][35][36], the nasal cavity and trachea [37][38][39][40][41][42][43][44], and excretory organs such as kidney and bladder [45][46][47][48]. Tight junctions and desmosomes are also detected in the alveolus epithelium [49][50][51].…”
Section: Types Of Epithelial Junctions and Their Tissue-specific Dist...mentioning
confidence: 99%
“…Hemidesmosomes are anchoring structures at the basement membrane that link intermediate filaments with the extracellular matrix via integrin proteins [20]. These types of junctions have been found in most of our major organs, including the epithelium of the skin [21][22][23][24][25], the digestive system (oral cavity, esophagus, stomach, and intestine) [26][27][28][29][30][31][32][33][34][35][36], the nasal cavity and trachea [37][38][39][40][41][42][43][44], and excretory organs such as kidney and bladder [45][46][47][48]. Tight junctions and desmosomes are also detected in the alveolus epithelium [49][50][51].…”
Section: Types Of Epithelial Junctions and Their Tissue-specific Dist...mentioning
confidence: 99%
“…Primary cell cultures were established from oral mucosal tissue obtained after third molar extractions as described recently [30]. In brief, the epithelial sheet and the connective tissue were separated by tissue digestion, then cut into small pieces prior to cell isolation through enzymatic treatment.…”
Section: Cell Culturementioning
confidence: 99%
“…A total of 15 studies, comprising 12 in vitro, 1 in vivo and 2 in vivo and in vitro studies, examined changes to individual α6 and/or β4 subunits at different stages of oral carcinogenesis [6,[24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Expression of α6 in OSCC and oral leukoplakia (OL) lesions was higher compared to normal mucosa, while β4 expression was increased in OSCC lesions with negligible changes in OL lesions [25].…”
Section: α6β4 Heterodimermentioning
confidence: 99%
“…A total of 12 studies, comprising 11 in vitro and 1 in vivo, specifically examined alterations in the hemidesmosomal integrin α6β4 heterodimer [24][25][26][27][28][29][30][33][34][35][36][37]. An in-vitro study on human primary OSCC tumours demonstrated increased α6β4 expression in aggressive lesions compared to non-metastatic growths, but reduced expression in PD and recurring tumours [27,34,36].…”
Section: α6β4 Heterodimermentioning
confidence: 99%